Silicon-based nano-particles as well as preparation method and application thereof
By adopting silicon-based nanoparticles with core-shell structures, the stability of SEI film is improved by using amorphous silicon-carbon composite shells, the problems of cyclic stability and low Coulomb efficiency of nanosilicon in lithium-ion batteries are solved, and efficient electrochemical performance improvement is achieved.
Patent Information
- Application Number
- CN202311368614.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-20
- Publication Date
- 2025-04-22
AI Technical Summary
The cycling stability and Coulombic efficiency of nanosilicon in lithium-ion batteries is low, mainly due to repeated rupture and growth of SEI membranes caused by volume expansion.
Silicon-based nanoparticles with core-shell structure are used, the core is amorphous silicon and the shell is an amorphous silicon carbon composite. The silicon and carbon elements are distributed in a gradient manner, and the silicon content gradually increases from the outside to the inside, and the carbon content gradually decreases. The silicon-based nanoparticles are prepared by thermal cracking reaction and co-cleaving reaction to form a stable SEI film to improve cycling performance.
The circulation performance and coulomb efficiency of silicon-based nanoparticles in lithium-ion batteries were significantly improved, and the capacity was increased to 2600-3600mAh/g. The first Coulomb efficiency reached 85%-92%, and the capacity retention rate was above 58% after 50 weeks of cycle.
Smart Images

Figure CN119864383A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of secondary batteries, and in particular relates to silicon-based nanoparticles and a preparation method and application thereof. Background Art
[0002] With the rapid development of lithium-ion battery technology, the specific capacity of artificial graphite anode is close to the theoretical specific capacity of graphite anode material (372mAh / g), but it still cannot meet the development needs of high energy density lithium-ion batteries. The theoretical specific capacity of silicon is as high as 4200mAh / g, which is more than 10 times that of graphite anode material. It has the advantages of low discharge platform and abundant resource reserves, and is considered to be the most promising new generation of anode material. However, silicon is accompanied by a huge volume expansion (~300%) during the lithium insertion process, which causes the electrode material to pulverize and detach from the current collector, showing poor cycle stability. Nano-sizing of silicon is an effective means to prevent silicon expansion and pulverization, improve cycle performance, and increase the utilization rate of active materials. Although nano-sizing can prevent silicon from pulverizing due to volume expansion, it cannot avoid the repeated rupture and growth of SEI film caused by volume expansion, which in turn causes the capacity of silicon anode to decay quickly, increase internal resistance, and reduce coulombic efficiency. Constructing a dense and stable SEI film on the surface is crucial to improving the cycle performance and coulombic efficiency of nano-silicon. Surface carbon coating is an important method for nano-silicon to build a stable SEI film. However, surface carbon coating will reduce the material's gram capacity, and the cycle performance needs to be further improved. Summary of the invention
[0003] Therefore, the technical problem to be solved by the present invention is to overcome the above-mentioned problems existing in nano-silicon in the prior art and to provide a silicon-based nanoparticle and a preparation method and application thereof.
[0004] To this end, the present invention provides the following technical solutions:
[0005] The invention provides a silicon-based nanoparticle, which has a core-shell structure, wherein the core is amorphous silicon, the shell is an amorphous silicon-carbon composite, and silicon and carbon elements in the shell are distributed in a gradient, and from the outside to the inside, the silicon content gradually increases and the carbon content gradually decreases.
[0006] Optionally, the particle size of the silicon-based nanoparticles is 25-250nm (e.g., 25nm, 30nm, 50nm, 100nm, 150nm, 200nm, 250nm, etc.), wherein the size of the core is 20-245nm (e.g., 20nm, 25nm, 50nm, 100nm, 150nm, 200nm, 245nm, etc.), and the thickness of the shell is 5-50nm (e.g., 5nm, 10nm, 15nm, 20nm, 30nm, 40nm, 50nm, etc.).
[0007] Optionally, in the amorphous silicon-carbon composite, the mass percentage of carbon is 1-15% (eg, 1%, 2%, 3%, 5%, 8%, 10%, 15%, etc.), and the mass percentage of oxygen is <2.0%.
[0008] The present invention also provides a method for preparing the above-mentioned silicon-based nanoparticles, comprising the following steps: subjecting silicon hydride compounds to a thermal cracking reaction at 380-640°C to obtain a reaction gas A containing amorphous silicon and silicon hydride compounds, cooling the reaction gas, mixing the reaction gas with hydrocarbons, and subjecting the reaction gas to a co-cracking reaction at 580-640°C.
[0009] Optionally, the device used in the process of preparing silicon-based nanoparticles includes a reaction system and a filtration system that are connected to each other, and the number of the filtration system is at least one; the reaction system includes a reactor furnace tube, and the reactor furnace tube is alternately provided with a first heating zone, a first cooling zone, a second heating zone, and a second cooling zone from top to bottom; the first reaction gas inlet is located at the top of the reactor furnace tube; the second reaction gas inlet is located in the first cooling zone.
[0010] Optionally, the device further comprises a sheath gas inlet, wherein the sheath gas inlet is an annular inlet and is arranged around the first reaction gas inlet;
[0011] And / or, a passivation gas inlet is also provided on the connecting pipeline between the reaction system and the filtering system.
[0012] Optionally, the silicon hydride is mixed with a carrier gas for feeding, and the volume proportion of the silicon hydride is 5-30% (e.g., 5%, 10%, 15%, 20%, 25%, 30%, etc.) based on the total amount of the silicon hydride and the carrier gas, and the flow rate is 40-100slm (e.g., 40slm, 50slm, 60slm, 70slm, 80slm, 90slm, 100slm, etc.);
[0013] And / or, the hydrocarbon is mixed with the carrier gas for feeding, and the volume proportion of the hydrocarbon is 0.5-20% (e.g., 0.5%, 1%, 5%, 10%, 15%, 20%, etc.) based on the total amount of the hydrocarbon and the carrier gas, and the flow rate is 0.5-20slm (e.g., 0.5slm, 1slm, 2slm, 5slm, 10slm, 15slm, 20slm, etc.);
[0014] And / or, the co-cracking reaction pressure is normal pressure or 1-2000 Pa higher than normal pressure;
[0015] And / or, after the co-cleavage reaction is completed, a passivation step is further included; the passivation step includes passing an inert gas and an oxygen-containing gas mixture to passivate the nanoparticles for 1-6 hours, the oxygen volume accounts for 3-10% (for example, 3%, 5%, 8%, 10%), and the flow rate is 5-50slm (for example, 5slm, 10slm, 15slm, 20slm, 30slm, 45slm, 50slm); the oxygen-containing gas is oxygen or air;
[0016] And / or, the silicon hydride compound includes at least one of monosilane, disilane and trisilane;
[0017] and / or, the hydrocarbon comprises at least one of methane, ethane, ethylene, acetylene, propylene, propyne, cyclohexane, benzene and toluene;
[0018] And / or, the carrier gas includes at least one of nitrogen, argon, hydrogen, and neon.
[0019] The present invention also provides a silicon-based nanoparticle having a core-shell structure, wherein the core is crystalline silicon and the shell is an amorphous silicon-carbon composite. The silicon and carbon elements in the shell are distributed in a gradient, and from the outside to the inside, the silicon content gradually increases and the carbon content gradually decreases.
[0020] Optionally, the particle size of the silicon-based nanoparticles is 25-200nm (e.g., 25nm, 30nm, 50nm, 100nm, 150nm, 200nm, etc.), wherein the size of the core is 20-195nm (e.g., 20nm, 25nm, 50nm, 100nm, 150nm, 195nm, etc.), and the thickness of the shell is 5-50nm (e.g., 5nm, 10nm, 15nm, 20nm, 30nm, 40nm, 50nm, etc.).
[0021] Optionally, in the amorphous silicon-carbon composite, the mass percentage of carbon is 1-15% (eg, 1%, 2%, 3%, 5%, 8%, 10%, 15%, etc.), and the mass percentage of oxygen is <2.0%.
[0022] The present invention also provides a method for preparing the above-mentioned silicon-based nanoparticles, comprising the following steps: subjecting silicon hydride compounds to thermal cracking reaction at 700-900°C to obtain reaction gas A containing nano-silicon and silicon hydride compounds, cooling, mixing with hydrocarbons, and subjecting to co-cracking reaction at 580-640°C.
[0023] Optionally, the device used in the process of preparing silicon-based nanoparticles includes a reaction system and a filtration system that are connected to each other, and the number of the filtration system is at least one; the reaction system includes a reactor furnace tube, and the reactor furnace tube is alternately provided with a first heating zone, a first cooling zone, a second heating zone, and a second cooling zone from top to bottom; the first reaction gas inlet is located at the top of the reactor furnace tube; the second reaction gas inlet is located in the first cooling zone.
[0024] Optionally, the device further comprises a sheath gas inlet, wherein the sheath gas inlet is an annular inlet and is arranged around the first reaction gas inlet;
[0025] And / or, a passivation gas inlet is also provided on the connecting pipeline between the reaction system and the filtering system.
[0026] Optionally, the silicon hydride is mixed with a carrier gas for feeding, and the volume proportion of the silicon hydride is 5-30% (e.g., 5%, 10%, 15%, 20%, 25%, 30%, etc.) based on the total amount of the silicon hydride and the carrier gas, and the flow rate is 40-100slm (e.g., 40slm, 50slm, 60slm, 70slm, 80slm, 90slm, 100slm, etc.);
[0027] And / or, the hydrocarbon is mixed with a carrier gas for feeding, and the volume proportion of the hydrocarbon is 0.5-20% (e.g., 0.5%, 1%, 5%, 210%, 15%, 20%, etc.) based on the total amount of the hydrocarbon and the carrier gas, and the flow rate is 0.5-20slm (e.g., 0.5slm, 1slm, 2slm, 5slm, 10slm, 15slm, 20slm, etc.);
[0028] And / or, the co-cracking reaction pressure is normal pressure or 1-2000 Pa higher than normal pressure;
[0029] And / or, after the co-cleavage reaction is completed, a passivation step is further included; the passivation step includes passing an inert gas and an oxygen-containing gas mixture to passivate the nanoparticles for 1-6 hours, the oxygen volume accounts for 3-10% (for example, 3%, 5%, 8%, 10%, etc.), and the flow rate is 5-50slm (for example, 5slm, 10slm, 15slm, 20slm, 30slm, 45slm, 50slm, etc.); the oxygen-containing gas is oxygen or air;
[0030] And / or, the silicon hydride compound includes at least one of monosilane, disilane and trisilane;
[0031] and / or, the hydrocarbon comprises at least one of methane, ethane, ethylene, acetylene, propylene, propyne, cyclohexane, benzene and toluene;
[0032] And / or, the carrier gas includes at least one of nitrogen, argon, hydrogen, and neon.
[0033] The present invention also provides a negative electrode material, comprising the silicon-based nanoparticles prepared by the above-mentioned preparation method.
[0034] The present invention also provides a silicon-carbon negative electrode material, which is composed of the above-mentioned silicon-based nanoparticles or the silicon-based nanoparticles prepared by the above-mentioned preparation method, graphite and amorphous carbon. Among them, the graphite can include natural graphite and artificial graphite, and the amorphous carbon can be obtained by high-temperature carbonization of carbon source precursors such as phenolic resin and asphalt.
[0035] The silicon-carbon negative electrode material provided by the present invention has an average particle size of 8 to 12 microns and a specific surface area of 1 to 6 m 2 / g, gram capacity 1200 ~ 1500mAh / g, first coulombic efficiency 88% -92%.
[0036] The present invention also provides a method for preparing the above-mentioned silicon-carbon negative electrode material, which can be prepared by a spraying method or an extrusion method, comprising the following steps:
[0037] S1, mixing silicon-based nanoparticles, a dispersant, graphite, a first carbon source, and a solvent to obtain a dispersion;
[0038] S2, spray drying the dispersion (spraying method) and performing a first heat treatment to obtain a precursor;
[0039] Alternatively, the dispersion is kneaded, the solvent is removed, extruded (extrusion method), and subjected to a first heat treatment to obtain a precursor;
[0040] S3, mixing the precursor with a second carbon source, performing a second heat treatment, classifying, and demagnetizing to obtain a silicon-carbon negative electrode material;
[0041] Optionally, the first carbon source is an alcohol-soluble polymer, preferably one or more of phenolic resin, polyvinyl pyrrolidone, and acrylic resin;
[0042] Optionally, the second carbon source includes one or more of asphalt, phenolic resin, gum arabic, coumarone resin, glucose, sucrose, and polyvinyl pyrrolidone;
[0043] Optionally, the solvent includes one or more of ethanol, methanol, n-propanol, isopropanol, n-butanol, tert-butanol, and isobutanol;
[0044] After the heat treatment, the first carbon source and the second carbon source are converted into amorphous carbon.
[0045] Specifically, with phenolic resin as the first carbon source and asphalt as the second carbon source, the spraying method includes the following steps:
[0046] S1: Silicon-based nanoparticles and anhydrous ethanol are uniformly mixed in a mass ratio of 0.1 to 0.25:1 and added to a horizontal sand mill to sand grind the silicon-based nanoparticles for 1 to 6 hours to obtain dispersion A. In order to prevent the nanopowder from reaggregating, a dispersant is added during the sand grinding process. The amount of the dispersant is 0.5 to 5% of the mass of the nanopowder. The dispersant can be a compound of one or more dispersants such as polyvinyl pyrrolidone, polyethylene glycol, ammonium polypropionate, and a polymer carboxylic acid block copolymer.
[0047] S2: Dispersion A is mixed with graphite and alcohol-soluble phenolic resin, and the mass ratio of silicon-based nanoparticles to graphite and alcohol-soluble phenolic resin is 3-5:3-5:2. After the alcohol-soluble phenolic resin is completely dissolved, dispersion B is obtained. Dispersion B is spray-dried to obtain precursor C.
[0048] S3: Perform a first heat treatment on precursor C to obtain precursor D, the first heat treatment temperature is 500-600°C, the heating rate is 1-5°C / min, the insulation time is 2-6h, and the atmosphere is a non-oxidizing atmosphere such as nitrogen, argon, helium, etc.
[0049] S4: Precursor D is mixed with asphalt to obtain precursor E, the asphalt softening point is 180-250°C, and the amount is 2-10% of the mass of precursor D. Precursor E is then subjected to a second heat treatment, the second heat treatment temperature is 700-800°C, the heating rate is 1-5°C / min, and the insulation time is 1-3h. The powder obtained after the second heat treatment is classified and demagnetized to obtain a finished silicon-carbon negative electrode material.
[0050] Specifically, using phenolic resin as the first carbon source and asphalt as the second carbon source, the extrusion method includes the following steps:
[0051] S1: Silicon-based nanoparticles and anhydrous ethanol are uniformly mixed in a mass ratio of 0.1 to 0.25:1, and the mixture is added to a horizontal sand mill to sand grind the silicon-based nanoparticles for 1 to 6 hours to obtain dispersion A. In order to prevent the nanopowder from reaggregating, a dispersant is added during the sand grinding process, and the amount of the dispersant is 0.5 to 5% of the mass of the nanopowder. The dispersant can be a compound of one or more dispersants such as polyvinyl pyrrolidone, polyethylene glycol 10000, ammonium polypropionate, and a polymer carboxylic acid block copolymer.
[0052] S2: Dispersion A is mixed with graphite and alcohol-soluble phenolic resin, and the mass ratio of silicon-based nanoparticles to graphite and alcohol-soluble phenolic resin is 3-5:3-5:2. After the alcohol-soluble phenolic resin is completely dissolved, dispersion B is obtained. Dispersion B is placed in a kneader for kneading, and precursor C is obtained after the solvent ethanol is evaporated.
[0053] S3: Precursor C is placed in a screw extruder for extrusion molding. Precursor C is subjected to jaw crushing, roller crushing, first heat treatment and air flow crushing treatment to obtain precursor D. The first heat treatment temperature is 500-600°C, the heating rate is 1-5°C / min, the holding time is 2-6h, and the atmosphere is a non-oxidizing atmosphere such as nitrogen, argon, helium, etc.
[0054] S4: Precursor D is mixed with asphalt to obtain precursor E, the asphalt softening point is 180-250°C, and the amount is 2-10% of the mass of precursor D. Precursor E is then subjected to a second heat treatment, the heat treatment temperature is 700-800°C, the heating rate is 1-5°C / min, the insulation time is 1-3h, and the atmosphere is a non-oxidizing atmosphere such as nitrogen, argon, helium, etc. The powder obtained after the second heat treatment is classified and demagnetized to obtain a finished silicon-carbon negative electrode material.
[0055] The present invention also provides a negative electrode plate, comprising: the above-mentioned negative electrode material, or the above-mentioned silicon-carbon negative electrode material, or the silicon-carbon negative electrode material prepared by the above-mentioned preparation method.
[0056] The present invention also provides a secondary battery, comprising the negative electrode plate.
[0057] In the present invention, the specific composition and preparation method of the secondary battery are conventional in the art and are not specifically limited herein.
[0058] The technical solution of the present invention has the following advantages:
[0059] The silicon-based nanoparticles provided by the present invention have a core-shell structure, wherein the core is amorphous silicon or crystalline silicon, and the shell is an amorphous silicon-carbon composite. The silicon and carbon elements in the shell are distributed in a gradient, and from the outside to the inside, the silicon content gradually increases, and the carbon content gradually decreases. The present invention uses an amorphous silicon-carbon composite as a coating layer. Compared with amorphous silicon or crystalline silicon, the amorphous silicon-carbon composite has a smaller volume expansion during the lithium insertion process and has better cycle performance; the interface compatibility between the silicon-carbon composite coating layer and silicon is significantly better than that of the pure carbon coating layer. The structure of the silicon-carbon composite coating layer with carbon-rich surface and silicon-rich interior makes it impossible for the coating layer to have an obvious interface with the silicon surface. Compared with the pure carbon coating layer (which has an obvious interface with silicon), it has better structural stability during lithium insertion and expansion; at the same time, compared with the carbon coating layer, the amorphous silicon-carbon composite as a coating layer has a lower carbon content and can also significantly improve the gram capacity of the material. The specific surface area of the silicon-based nanoparticles provided is 8-25m 2 / g, used as negative electrode material for lithium batteries, with a gram capacity of 2600-3600mAh / g, an initial coulombic efficiency of 85%-92%, and a capacity retention rate of more than 58% after 50 cycles.
[0060] The preparation method of silicon-based nanoparticles provided by the present invention can realize co-cracking of silicon hydride and hydrocarbon at a relatively low temperature (crystallization temperature of amorphous silicon is below 650°C), realize coating of amorphous silicon, and avoid conversion of amorphous silicon into crystalline silicon.
[0061] The method for preparing silicon-based nanoparticles provided by the present invention adopts a device including a reaction system and a filtering system connected to each other, wherein the number of the filtering system is at least one; the reaction system includes a reactor furnace tube, wherein the reactor furnace tube is alternately provided with a first heating zone, a first cooling zone, a second heating zone, and a second cooling zone from top to bottom; a first reaction gas inlet is located at the top of the reactor furnace tube; and a second reaction gas inlet is located in the first cooling zone. In a conventional reactor, the nano-silicon particles generated during the reaction process collide with each other and are very easy to agglomerate into large particles. The reaction furnace tubes of the present invention are alternately provided as above, and after the nano-silicon is generated in the first heating zone, it is rapidly cooled in the first cooling zone, which can largely avoid the nano-silicon from violently colliding and agglomerating into large particles, and then the nano-silicon can be directly in the second heating zone to achieve in-situ surface coating.
[0062] The silicon-carbon negative electrode material provided by the present invention is composed of silicon-based nanoparticles, graphite and amorphous carbon. The average particle size of the silicon-carbon negative electrode material is 8 to 12 microns, and the specific surface area is 1 to 6 m 2 / g, gram capacity of 1200-1500mAh / g, first coulomb efficiency of 88%-92%. Compared with the silicon-carbon negative electrode material prepared with carbon-coated nano-silicon as raw material, the silicon-carbon negative electrode material prepared with the silicon-based nanoparticles provided by the present invention as raw material shows better cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0063] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0064] Figure 1 Schematic diagram of the reaction device structure used in the embodiment of the present invention;
[0065] Figure 2 is the X-ray photoelectron spectroscopy depth profiling test result of the product obtained in Example 1 of the present invention;
[0066] Reference numerals:
[0067] 100. Reactor system; 200. Filter system A; 300. Filter system B; 1. Reaction gas inlet; 2. Sheath gas inlet; 3. Pressure gauge; 4. Reactor furnace tube; 5. First heating system; 6. First cladding gas inlet; 7. Second cladding gas inlet; 8. First cooling system; 9. Second heating system; 10. Second cooling system; 11. First valve; 12. Second valve; 13. First passivation gas inlet; 14. Second passivation gas inlet; 15. Stainless steel corrugated connecting pipe; 16. Filter element; 17. Powder collection tank; 18. First exhaust gas outlet; 19. Second exhaust gas outlet. DETAILED DESCRIPTION
[0068] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.
[0069] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.
[0070] Example 1
[0071] This embodiment provides a silicon-based nanoparticle with a core-shell structure, wherein the core is nano-amorphous silicon and the shell is a silicon-carbon composite. Figure 1 The reaction device shown (the present invention is not limited to Figure 1 The device shown in the figure, other devices capable of realizing two-step reaction or devices respectively provided with two reactors can also be used in the present invention) to carry out the reaction, and the specific operation steps are as follows:
[0072] First, nitrogen is introduced through the sheath gas inlet 2 (annular inlet) to purge the reaction device, with a gas flow rate of 80 slm and a purge time of not less than 1 hour to ensure that the oxygen content in the reaction device is less than 5 ppm. After the purge is completed, the sheath gas needs to be continued to be introduced as a carrier gas. Subsequently, the first cooling system 8 and the second cooling system 10 are opened, and the first heating system 5 and the second heating system 9 of the reaction device are heated. The first heating system is set to a heating temperature of 600°C, and the second heating system is set to a heating temperature of 640°C. After the temperature of the heating zone is heated to the set temperature, acetylene / nitrogen mixed gas is introduced from the two-way sheath gas inlet (the first sheath gas inlet 6 and the second sheath gas inlet 7), and the gas flow rate of each way is 5 slm, and the acetylene volume content is 2%. Subsequently, silane is introduced through the reaction gas inlet 1 to start the reaction, with a flow rate of 10 slm. After reacting for 1 hour, the reaction gas inlet is closed, the coating gas inlet is closed, and the sheath gas is continued to be introduced for 1 hour to ensure that the unreacted silane and products in the entire reaction device are all purged out of the reaction system 100 and enter the filter system A200 through the stainless steel corrugated connecting pipe 15. Then close the first valve 11 connected between the reactor system and the filter system A200, close the sheath gas inlet, open the first passivation gas inlet 13, the passivation gas is an oxygen-nitrogen mixed gas with an oxygen content of 5% and a flow rate of 20slm. After passing the passivation gas for 1 hour, turn off the passivation gas. After standing for 1 hour, open the powder collection tank 17, collect the product, and obtain 723 grams of nano powder. The reaction tail gas is filtered through the filter element 16 (metal sintered filter element or ceramic sintered filter element) and discharged through the first tail gas outlet 18.
[0073] In this embodiment, the reaction process can also be carried out continuously, that is, after a certain reaction time, the first valve 11 is closed and the second valve 12 is opened, the powder collected in the filter system A 200 is passivated and discharged, and the filter system B 300 continues to filter and collect the product from the reaction system 100.
[0074] The test results show that the obtained nano powder has an oxygen content of 1.2%, a carbon content of 5.6%, a particle size of 30-180 nanometers, and a specific surface area of 16.7m 2 / g. Figure 2 As shown, the results of X-ray photoelectron spectroscopy depth analysis test show that the interior of the silicon-based nanoparticles is pure silicon, and the surface is covered with a layer of silicon-carbon composite. The carbon content gradually decreases from the surface to the inside and decreases to almost zero at a depth of about 20 nanometers. The oxygen element is mainly distributed on the surface of the nanocomposite.
[0075] The prepared nanopowder was mixed with sodium carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), and Super P conductive carbon black in a mass ratio of 60:7.2:12.8:20 to form a slurry with a solid content of 15%. The slurry was then evenly scraped onto the current collector copper foil, dried, and the pole pieces were cut. The button cell was assembled in a glove box with Ar atmosphere, using metallic lithium as the counter electrode and 1M LiPF6 (the volume ratio of ethylene carbonate to diethyl carbonate was 1:1) solution as the electrolyte to assemble a CR2032 battery. The obtained battery was tested on the battery test system according to the following test steps for the lithium storage performance of the nano-amorphous silicon / silicon-carbon composite: 0.1C constant current discharge to 1mV, 0.01C constant current discharge to 1mV, 0.05C constant current discharge to 1mV, 0.1C constant current charge to 1.5V, and two cycles. Subsequently, the cycling performance of the nano-amorphous silicon / silicon-carbon composite was tested in the following steps: 0.1C constant current discharge to 1mV, 1C constant current charge to 1.5V, and cycled for 50 cycles. The gram capacity of the nano-amorphous silicon / silicon-carbon composite was measured to be 3105mAh / g, the first efficiency was 88.1%, and after 50 cycles, the capacity retention rate was 68%.
[0076] Example 2
[0077] This embodiment provides a silicon-based nanoparticle with a core-shell structure, wherein the core is nano-amorphous silicon and the shell is a silicon-carbon composite. Figure 1 The reaction device shown in the figure is used for the reaction, and the specific operation steps are as follows:
[0078] First, nitrogen is introduced through the sheath gas inlet to purge the reaction device, with a gas flow rate of 80 slm and a purge time of not less than 1 hour to ensure that the oxygen content in the reaction device is less than 5ppm. After the purge is completed, the sheath gas is continued to be introduced as a carrier gas. Then, the circulating cooling water of the reaction device is turned on, and the first heating system and the second heating system of the reaction device are heated, and the heating temperatures are set to 550℃ and 640℃ respectively. After the temperature of the heating zone is heated to the set temperature, acetylene / nitrogen mixed gas is introduced from the two sheath gas inlets, with 5 slm for each gas and 2% acetylene content. Subsequently, silane is introduced through the reaction gas inlet to start the reaction, with a flow rate of 10 slm. After reacting for 1 hour, the reaction gas inlet is closed, the sheath gas inlet is closed, and the sheath gas is continued to be introduced for 1 hour to ensure that all unreacted silane and products in the entire reaction device are purged out of the reaction system. Then, the valve connecting the reactor system and the filter system was closed, the sheath gas inlet was closed, and the passivation gas inlet was opened. The passivation gas was an oxygen-nitrogen mixed gas with an oxygen content of 5% and a flow rate of 20 slm. After the passivation gas was introduced for 1 hour, the passivation gas was turned off. After standing for 1 hour, the powder collection tank was opened to collect the product, and 730 grams of nano powder was obtained.
[0079] The nano powder was tested according to the method of Example 1. The carbon content, oxygen content, particle size, and specific surface area of the nano powder were 7.1%, 1.1%, 30-200 nanometers, and 17.4 m 2 / g, gram capacity 2978mAh / g, first efficiency 89.5%, capacity retention rate 72% after 50 cycles.
[0080] Example 3
[0081] This embodiment provides a silicon-based nanoparticle with a core-shell structure, wherein the core is nano-amorphous silicon and the shell is a silicon-carbon composite. Figure 1 The reaction device shown in the figure is used for the reaction, and the specific operation steps are as follows:
[0082] First, nitrogen is introduced through the sheath gas inlet to purge the reaction device, with a gas flow rate of 75slm and a purge time of not less than 1h to ensure that the oxygen content in the reaction device is less than 5ppm. After the purge is completed, the sheath gas needs to be continued to be introduced as a carrier gas. Then, the circulating cooling water of the reaction device is turned on, and the first heating system and the second heating system of the reaction device are heated, and the heating temperatures are set to 600℃ and 640℃ respectively. After the temperature of the heating zone is heated to the set temperature, acetylene / nitrogen mixed gas is introduced from the two sheath gas inlets, with 5slm for each gas and 2% acetylene content. Subsequently, silane is introduced through the reaction gas inlet to start the reaction, with a flow rate of 15slm. After reacting for 1h, the reaction gas inlet is turned off, the sheath gas inlet is turned off, and the sheath gas is continued to be introduced for 1h to ensure that all unreacted silane and products in the entire reaction device are purged out of the reaction system. Then, the valve connecting the reactor system and the filter system was closed, the sheath gas inlet was closed, and the passivation gas inlet was opened. The passivation gas was an oxygen-nitrogen mixed gas with an oxygen content of 5% and a flow rate of 20 slm. After the passivation gas was introduced for 1 hour, the passivation gas was turned off. After standing for 1 hour, the powder collection tank was opened to collect the product, and 1034 grams of nano powder was obtained.
[0083] The test was carried out according to the method of Example 1. The obtained nano powder had a carbon content of 3.5%, an oxygen content of 1.8%, a particle size of 30-180 nanometers, and a specific surface area of 14.7 m 2 / g, gram capacity 3218mAh / g, first efficiency 87.6%, capacity retention rate 61% after 50 cycles.
[0084] Example 4
[0085] This embodiment provides a silicon-based nanoparticle with a core-shell structure, wherein the core is nano-amorphous silicon and the shell is a silicon-carbon composite. Figure 1 The reaction device shown in the figure is used for the reaction, and the specific operation steps are as follows:
[0086] First, nitrogen is introduced through the sheath gas inlet to purge the reaction device, with a gas flow rate of 80 slm and a purge time of not less than 1 hour to ensure that the oxygen content in the reaction device is less than 5 ppm. After the purge is completed, the sheath gas needs to be continued to be introduced as a carrier gas. Then, the circulating cooling water of the reaction device is turned on, and the first heating system and the second heating system of the reaction device are heated, and the heating temperatures are set to 600°C and 640°C respectively. After the temperature of the heating zone is heated to the set temperature, acetylene / nitrogen mixed gas is introduced from the two sheath gas inlets, with 5 slm for each gas and 5% acetylene content. Subsequently, silane is introduced through the reaction gas inlet to start the reaction, with a flow rate of 10 slm. After reacting for 1 hour, the reaction gas inlet is turned off, the sheath gas inlet is turned off, and the sheath gas is continued to be introduced for 1 hour to ensure that all unreacted silane and products in the entire reaction device are purged out of the reaction system. Then, the valve connecting the reactor system and the filter system was closed, the sheath gas inlet was closed, and the passivation gas inlet was opened. The passivation gas was an oxygen-nitrogen mixed gas with an oxygen content of 10% and a flow rate of 30 slm. After the passivation gas was introduced for 1 hour, the passivation gas was turned off. After standing for 1 hour, the powder collection tank was opened to collect the product, and 704 grams of nano powder was obtained.
[0087] The test was carried out according to the method of Example 1. The obtained nano powder had a carbon content of 9.3%, an oxygen content of 1.9%, a particle size of 30-230 nanometers, and a specific surface area of 15.7 m 2 / g, gram capacity 2803mAh / g, first efficiency 86.1%, capacity retention rate 74% after 50 cycles.
[0088] Example 5
[0089] This embodiment provides a silicon-based nanoparticle with a core-shell structure, wherein the core is nanocrystalline silicon and the shell is a silicon-carbon composite. Figure 1 The reaction device shown in the figure is used for the reaction, and the specific operation steps are as follows:
[0090] First, nitrogen is introduced through the sheath gas inlet to purge the reaction device, with a gas flow rate of 90 slm and a purge time of not less than 1 hour to ensure that the oxygen content in the reaction device is less than 5ppm. After the purge is completed, the sheath gas needs to be continued to be introduced as a carrier gas. Then, the circulating cooling water of the reaction device is turned on, and the first heating system and the second heating system of the reaction device are heated, and the heating temperatures are set to 800℃ and 640℃ respectively. After the temperature of the heating zone is heated to the set temperature, acetylene / nitrogen mixed gas is introduced from the two sheath gas inlets, with 5 slm for each gas and 2% acetylene content. Subsequently, silane is introduced through the reaction gas inlet to start the reaction, with a flow rate of 10 slm. After reacting for 1 hour, the reaction gas inlet is turned off, the sheath gas inlet is turned off, and the sheath gas is continued to be introduced for 1 hour to ensure that all unreacted silane and products in the entire reaction device are purged out of the reaction system. Then, the valve connecting the reactor system and the filter system was closed, the sheath gas inlet was closed, and the passivation gas inlet was opened. The passivation gas was an oxygen-nitrogen mixed gas with an oxygen content of 5% and a flow rate of 20 slm. After the passivation gas was introduced for 1 hour, the passivation gas was turned off. After standing for 1 hour, the powder collection tank was opened to collect the product, and 708 grams of nano powder was obtained.
[0091] The test was carried out according to the method of Example 1. The obtained nano powder had a carbon content of 5.1%, an oxygen content of 1.1%, a particle size of 25-160 nanometers, and a specific surface area of 12.6 m 2 / g, gram capacity 3250mAh / g, first efficiency 91.7%, capacity retention rate 58% after 50 cycles.
[0092] Example 6
[0093] This embodiment provides a silicon-carbon negative electrode material. Silicon-based nanoparticles are prepared according to the method of Embodiment 1. The silicon-carbon negative electrode material is prepared by a spraying method. The specific steps are as follows:
[0094] First, 20g of polyethylene glycol 10000, 1kg of silicon-based nanoparticles and 4kg of anhydrous ethanol were mixed and added to a horizontal sand mill. The sand mill was started and run for 1h to obtain dispersion A. Subsequently, dispersion A was mixed with 1kg of artificial graphite and 500g of phenolic resin 2123 and stirred until the phenolic resin was completely dissolved to obtain dispersion B. Dispersion B was spray dried to obtain precursor C. Precursor C was heat treated to obtain precursor D, the heat treatment temperature was 600℃, the heating rate was 3℃ / min, the insulation time was 4h, and the heat treatment atmosphere was nitrogen. Subsequently, precursor D was mixed with asphalt with a softening point of 200℃ in a mass ratio of 92:8, and after being mixed evenly, it was heat treated in a nitrogen atmosphere, the heat treatment temperature was 800℃, the heating rate was 3℃ / min, and the insulation time was 2 hours. Finally, the obtained powder was graded and demagnetized to obtain the final silicon-carbon negative electrode material. After testing, the average particle size of the silicon-carbon negative electrode material obtained was 8.7 microns and the specific surface area was 3.2m2 / g.
[0095] The prepared silicon-carbon negative electrode material was mixed with sodium carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), and Super P conductive carbon black in a mass ratio of 80:4:6:10 to form a slurry with a solid content of 30%. The slurry was then evenly scraped onto the current collector copper foil, dried, and the pole pieces were cut. The button cell was assembled in a glove box with an Ar atmosphere, using metallic lithium as the counter electrode and 1M LiPF6 (the volume ratio of ethylene carbonate to diethyl carbonate is 1:1) solution as the electrolyte to assemble a CR2032 battery. The obtained battery was tested on the battery test system according to the following test steps for the lithium storage performance of the silicon-carbon negative electrode material: 0.1C constant current discharge to 1mV, 0.01C constant current discharge to 1mV, 0.05C constant current discharge to 1mV, 0.1C constant current charge to 1.5V, and two cycles. Subsequently, the cycle performance of the silicon-carbon negative electrode material was tested in the following steps: 0.1C constant current discharge to 1mV, 1C constant current charge to 1.5V, and cycled for 50 cycles. The gram capacity of the silicon-carbon negative electrode was measured to be 1457mAh / g, the first efficiency was 91.3%, and after 50 cycles, the capacity retention rate was 95%.
[0096] Example 7
[0097] This embodiment provides a silicon-carbon negative electrode material. Silicon-based nanoparticles are prepared according to the method of Embodiment 1. The silicon-carbon negative electrode material is prepared by extrusion method. The specific steps are as follows:
[0098] First, 20g of polyethylene glycol 10000, 1kg of silicon-based nanoparticles and 4kg of anhydrous ethanol were mixed evenly and added to a horizontal sand mill. The sand mill was started and run for 1h to obtain dispersion A. Subsequently, dispersion A was mixed with 1kg of artificial graphite and 500g of phenolic resin 2123 and stirred until the phenolic resin was completely dissolved to obtain dispersion B. Dispersion B was added to a kneader for kneading and drying to obtain precursor C. Precursor C was added to an extrusion screw machine for extrusion molding. The extruded precursor C was subjected to jaw crushing, roller crushing, heat treatment and air flow crushing to obtain precursor D. The heat treatment temperature was 600°C, the heating rate was 3°C / min, the insulation time was 4h, and the heat treatment atmosphere was argon. Subsequently, the precursor D was mixed with asphalt with a softening point of 200°C at a mass ratio of 92:8. After being evenly mixed, it was heat treated in a nitrogen atmosphere at a temperature of 800°C, a heating rate of 3°C / min, and a holding time of 3h. Finally, the obtained powder was classified and demagnetized to obtain the final silicon-carbon negative electrode material.
[0099] According to the method of Example 6, a CR2032 battery was assembled and tested. The average particle size of the obtained silicon-carbon negative electrode material was 11.5 μm, and the specific surface area was 4.7 m2 / g, the gram capacity is 1376mAh / g, the first efficiency is 90.8%, and after 50 cycles, the capacity retention rate is 94%.
[0100] Example 8
[0101] This embodiment provides a silicon-carbon negative electrode material. Silicon-based nanoparticles are prepared according to the method of Example 5, and silicon-carbon negative electrode materials are prepared and tested according to the method of Example 6. After testing, the average particle size of the obtained silicon-carbon negative electrode material is 9.1 microns, and the specific surface area is 3.5m 2 / g, the gram capacity is 1328mAh / g, the first efficiency is 90.3%, and after 50 cycles, the capacity retention rate is 91%.
[0102] Comparative Example 1
[0103] This comparative example provides a method for preparing nano-amorphous silicon by using Figure 1 The reaction device shown in the figure is used for the reaction, and the specific operation steps are as follows:
[0104] First, nitrogen is introduced through the sheath gas inlet to purge the reaction device, with a gas flow rate of 40 slm and a purge time of not less than 1 hour to ensure that the oxygen content in the reaction device is less than 5 ppm. After the purge is completed, the sheath gas needs to be continued to be introduced as the carrier gas for the reaction gas. Then, the circulating cooling water of the reaction device is turned on, and the first heating system of the reaction device is heated, and the heating temperature is set to 640°C, and the second heating system is kept closed. After the temperature of the first heating system rises to the set temperature, nitrogen is introduced from the two sheath gas inlets as cooling gas, with 5 slm for each gas. Then, silane is introduced through the reaction gas inlet to start the reaction, with a flow rate of 10 slm. After reacting for 1 hour, the reaction gas inlet is closed, the sheath gas inlet is closed, and the sheath gas inlet is continued to be introduced for 1 hour to ensure that all unreacted silane in the entire reaction device is purged out of the reaction system. Then, the valve connecting the reactor system and the filter system is closed, the sheath gas inlet is closed, and the passivation gas inlet is opened. The passivation gas is an oxygen-nitrogen mixed gas with an oxygen content of 5% and a flow rate of 20 slm. After the passivation gas was introduced for 1 hour, the passivation gas was turned off. After standing for 1 hour, the powder collection tank was opened to collect the product nano amorphous powder, and 690 grams of nano powder was obtained.
[0105] The test was carried out according to the method of Example 1. The obtained nano powder had an oxygen content of 3.5%, a particle size of 25-250 nanometers, and a specific surface area of 18.9 m 2 / g, gram capacity 3420mAh / g, first efficiency 85.7%, capacity retention rate 52% after 50 cycles.
[0106] Comparative Example 2
[0107] This comparative example provides a preparation method of nanocrystalline silicon by using Figure 1The reaction device shown in the figure is used for the reaction, and the specific operation steps are as follows:
[0108] First, nitrogen is introduced through the sheath gas inlet to purge the reaction device, with a gas flow rate of 40 slm and a purge time of not less than 1 hour to ensure that the oxygen content in the reaction device is less than 5 ppm. After the purge is completed, the sheath gas needs to be continued to be introduced as the carrier gas for the reaction gas. Then, the circulating cooling water of the reaction device is turned on, and the first heating system of the reaction device is heated, and the heating temperature is set to 800°C, and the second heating system is kept closed. After the temperature of the first heating system rises to the set temperature, nitrogen is introduced from the two sheath gas inlets as cooling gas, with 5 slm for each gas. Then, silane is introduced through the reaction gas inlet to start the reaction, with a flow rate of 10 slm. After reacting for 1 hour, the reaction gas inlet is closed, the sheath gas inlet is closed, and the sheath gas inlet is continued to be introduced for 1 hour to ensure that all unreacted silane in the entire reaction device is purged out of the reaction system. Then, the valve connecting the reactor system and the filter system is closed, the sheath gas inlet is closed, and the passivation gas inlet is opened. The passivation gas is an oxygen-nitrogen mixed gas with an oxygen content of 5% and a flow rate of 20 slm. After the passivation gas was introduced for 1 hour, the passivation gas was turned off. After standing for 1 hour, the powder collection tank was opened to collect the product nanocrystalline silicon powder, and 703 grams of nano powder was obtained.
[0109] The test was carried out according to the method of Example 1. The obtained nano powder had an oxygen content of 0.9%, a particle size of 25-150 nanometers, and a specific surface area of 9.8 m 2 / g, gram capacity 3630mAh / g, first efficiency 92.1%, capacity retention rate 35% after 50 cycles.
[0110] Comparative Example 3
[0111] This comparative example provides a silicon-based nanoparticle with a core-shell structure, wherein the core is nanocrystalline silicon and the shell is carbon. Figure 1 The reaction device shown in the figure is used for the reaction, and the specific operation steps are as follows:
[0112] First, nitrogen is introduced through the sheath gas inlet to purge the reaction device, with a gas flow rate of 40slm and a purge time of not less than 1h to ensure that the oxygen content in the reaction device is less than 5ppm. After the purge is completed, the sheath gas must be continued to be introduced as a carrier gas for the reaction gas. Then, the circulating cooling water of the reaction device is turned on, and the first heating system and the second heating system of the reaction device are heated, and the heating temperature is set to 640℃. After the temperature of the heating zone is heated to the set temperature, a nitrogen / acetylene mixed gas is introduced from the two sheath gas inlets, with an acetylene content of 20% and 5slm for each gas. Subsequently, silane is introduced through the reaction gas inlet to start the reaction, with a flow rate of 10slm. After reacting for 1h, the reaction gas inlet is turned off, the sheath gas inlet is turned off, and the sheath gas is continued to be introduced for 1h to ensure that all unreacted silane and products in the entire reaction device are purged out of the reaction system. Then, the valve connecting the reactor system and the filter system was closed, the sheath gas inlet was closed, and the passivation gas inlet was opened. The passivation gas was an oxygen-nitrogen mixed gas with an oxygen content of 5% and a flow rate of 20 slm. After the passivation gas was introduced for 1 hour, the passivation gas was turned off. After standing for 1 hour, the powder collection tank was opened to collect the product carbon-coated crystalline silicon nanopowder, and 735 grams of nanopowder was obtained.
[0113] The nano powder was tested according to the method of Example 1. The carbon content, oxygen content and particle size of the nano powder were 1.2%, 1.3%, 30-150 nanometers and 17.6 m3 respectively. 2 / g, gram capacity 3102mAh / g, first efficiency 86.3%, capacity retention rate 55% after 50 cycles.
[0114] Comparative Example 4
[0115] This comparative example provides a silicon-carbon negative electrode material. Silicon-based nanoparticles are prepared according to the method of comparative example 3, and silicon-carbon negative electrode materials are prepared and tested according to the method of example 6. After testing, the average particle size of the obtained silicon-carbon negative electrode material is 9.3 microns, and the specific surface area is 3.7 m 2 / g, the gram capacity is 1316mAh / g, the first efficiency is 90.1%, and after 50 cycles, the capacity retention rate is 88%.
[0116] The carbon content and electrochemical performance data of the samples in the examples and comparative examples are summarized in Table 1:
[0117] Table 1
[0118]
[0119]
[0120] By analyzing the experimental data in the above table, it can be seen that: compared with the data of comparative examples 1-2, the cycle performance of nano-amorphous silicon is significantly better than that of nano-crystalline silicon. Comparative examples 1-5 and the data of comparative examples 1 and 2 show that, whether nanocrystalline or nano-amorphous silicon, the cycle performance is significantly improved after the surface is coated with a silicon-carbon composite. Comparative example 1 and comparative example 3 show that, under similar carbon content, the cycle performance of nano-amorphous silicon coated with amorphous silicon-carbon composite is significantly better than that of pure carbon-coated nano-amorphous silicon. The reason is that the interface compatibility between the silicon-carbon composite coating and silicon is significantly better than that of the pure carbon coating. The structure of the silicon-carbon composite coating with carbon-rich surface and silicon-rich interior makes the coating have no obvious interface with the surface of silicon. Compared with the pure carbon coating (which has an obvious interface with silicon), it has better structural stability when lithium is embedded and expanded. By comparing the results of Examples 6-8 with Comparative Example 4, it can be seen that the silicon-carbon negative electrode material prepared using silicon-based nanoparticles as the silicon source shows better cycle performance. The reason is that the surface carbon-rich and internal silicon-rich structure of the silicon-based nanoparticles in the silicon-carbon negative electrode material makes the silicon-based nanoparticles have better interface compatibility with amorphous carbon, better interface stability, and better structural stability during lithium insertion expansion.
[0121] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the scope of protection of the invention.
Claims
1. A silicon-based nanoparticle, characterized in that: The silicon-based nanoparticles have a core-shell structure, the core is amorphous silicon, the shell is an amorphous silicon-carbon composite, and the silicon and carbon elements in the shell are distributed in a gradient, with the silicon content gradually increasing and the carbon content gradually decreasing from the outside to the inside.
2. The silicon-based nanoparticles according to claim 1, characterized in that The particle size of the silicon-based nanoparticles is 25-250 nm, wherein the size of the core is 20-245 nm and the thickness of the shell is 5-50 nm; And / or, in the amorphous silicon-carbon composite, the mass percentage of carbon is 1-15%, and the mass percentage of oxygen is less than 2.0%.
3. A method for preparing silicon-based nanoparticles according to any one of claims 1 to 2, characterized in that: The method comprises the following steps: subjecting silicon hydride to thermal cracking reaction at 380-640°C to obtain reaction gas A containing amorphous silicon and silicon hydride, cooling the reaction gas, mixing the reaction gas with hydrocarbons, and subjecting the reaction gas to co-cracking reaction at 580-640°C.
4. The method for preparing silicon-based nanoparticles according to claim 3, characterized in that: The device used in the preparation process of the silicon-based nanoparticles includes a reaction system and a filtering system connected to each other, and the number of the filtering system is at least one; the reaction system includes a reactor furnace tube, and the reactor furnace tube is alternately provided with a first heating zone, a first cooling zone, a second heating zone, and a second cooling zone from top to bottom; A first reaction gas inlet is located at the top of the reactor furnace tube; The second reaction gas inlet is located in the first cooling zone.
5. The method for preparing silicon-based nanoparticles according to any one of claims 3 to 4, characterized in that: Silicon hydride and carrier gas are mixed and fed, and the volume proportion of silicon hydride is 5-30% based on the total amount of silicon hydride and carrier gas, and the flow rate is 40-100slm; And / or, hydrocarbons are mixed with carrier gas for feeding, the volume proportion of hydrocarbons is 0.5-20% based on the total amount of hydrocarbons and carrier gas, and the flow rate is 0.5-20slm; And / or, the co-cracking reaction pressure is normal pressure or 1-2000 Pa higher than normal pressure; And / or, after the co-cleavage reaction is completed, a passivation step is further included; the passivation step includes passing an inert gas and an oxygen-containing gas mixture into the nanoparticles for a passivation treatment for 1-6 hours, wherein the oxygen volume accounts for 3-10% and the flow rate is 5-50slm; the oxygen-containing gas is oxygen or air; And / or, the silicon hydride compound includes at least one of monosilane, disilane and trisilane; and / or, the hydrocarbon comprises at least one of methane, ethane, ethylene, acetylene, propylene, propyne, cyclohexane, benzene and toluene; And / or, the carrier gas includes at least one of nitrogen, argon, hydrogen, and neon.
6. A silicon-based nanoparticle, characterized in that: The silicon-based nanoparticles have a core-shell structure, the core is crystalline silicon, the shell is an amorphous silicon-carbon composite, and the silicon and carbon elements in the shell are distributed in a gradient, with the silicon content gradually increasing and the carbon content gradually decreasing from the outside to the inside.
7. The silicon-based nanoparticles according to claim 6, characterized in that The particle size of the silicon-based nanoparticles is 25-200 nm, wherein the size of the core is 20-195 nm and the thickness of the shell is 5-50 nm; And / or, in the amorphous silicon-carbon composite, the mass percentage of carbon is 1-15%, and the mass percentage of oxygen is less than 2.0%.
8. A method for preparing silicon-based nanoparticles according to claim 6 or 7, characterized in that: The method comprises the following steps: subjecting silicon hydride to thermal cracking reaction at 700-900 DEG C to obtain reaction gas A containing nano silicon and silicon hydride, cooling, mixing with hydrocarbon, and subjecting to co-cracking reaction at 580-640 DEG C.
9. The method for preparing silicon-based nanoparticles according to claim 8, characterized in that: The device used in the preparation process of the silicon-based nanoparticles includes a reaction system and a filtering system connected to each other, and the number of the filtering system is at least one; the reaction system includes a reactor furnace tube, and the reactor furnace tube is alternately provided with a first heating zone, a first cooling zone, a second heating zone, and a second cooling zone from top to bottom; A first reaction gas inlet is located at the top of the reactor furnace tube; The second reaction gas inlet is located in the first cooling zone.
10. The method for preparing silicon-based nanoparticles according to any one of claims 8 to 9, characterized in that: Silicon hydride and carrier gas are mixed and fed, and the volume proportion of silicon hydride is 5-30% based on the total amount of silicon hydride and carrier gas, and the flow rate is 40-100slm; And / or, hydrocarbons are mixed with carrier gas for feeding, the volume proportion of hydrocarbons is 0.5-20% based on the total amount of hydrocarbons and carrier gas, and the flow rate is 0.5-20slm; And / or, the co-cracking reaction pressure is normal pressure or 1-2000 Pa higher than normal pressure; And / or, after the co-cleavage reaction is completed, a passivation step is further included; the passivation step includes passing an inert gas and an oxygen-containing gas mixture into the nanoparticles for a passivation treatment for 1-6 hours, wherein the oxygen volume accounts for 3-10% and the flow rate is 5-50slm; the oxygen-containing gas is oxygen or air; And / or, the silicon hydride compound includes at least one of monosilane, disilane and trisilane; and / or, the hydrocarbon comprises at least one of methane, ethane, ethylene, acetylene, propylene, propyne, cyclohexane, benzene and toluene; And / or, the carrier gas includes at least one of nitrogen, argon, hydrogen, and neon.
11. A negative electrode material, characterized in that: The invention comprises the silicon-based nanoparticles as described in any one of claims 1-2 and 6-7 or the silicon-based nanoparticles prepared by the preparation method as described in any one of claims 3-5 and 8-10.
12. A silicon-carbon negative electrode material, characterized in that: A composite of the silicon-based nanoparticles according to any one of claims 1-2, 6-7 or the silicon-based nanoparticles prepared by the preparation method according to any one of claims 3-5, 8-10, graphite and amorphous carbon; Optionally, the silicon-carbon negative electrode material has an average particle size of 8 to 12 microns and a specific surface area of 1 to 6 m 2 / g, gram capacity 1200 ~ 1500mAh / g, first coulombic efficiency 88% -92%.
13. A method for preparing the silicon-carbon negative electrode material according to claim 12, characterized in that: The following steps are involved: S1, mixing silicon-based nanoparticles, a dispersant, graphite, a first carbon source, and a solvent to obtain a dispersion; S2, spray drying the dispersion and performing a first heat treatment to obtain a precursor; Alternatively, the dispersion is kneaded, the solvent is removed, extruded, and subjected to a first heat treatment to obtain a precursor; S3, mixing the precursor with a second carbon source, performing a second heat treatment, classifying, and demagnetizing to obtain a silicon-carbon negative electrode material; Optionally, the first carbon source is an alcohol-soluble polymer, preferably one or more of phenolic resin, polyvinyl pyrrolidone, and acrylic resin; Optionally, the second carbon source includes one or more of asphalt, phenolic resin, gum arabic, coumarone resin, glucose, sucrose, and polyvinyl pyrrolidone; Optionally, the solvent includes one or more of ethanol, methanol, n-propanol, isopropanol, n-butanol, tert-butanol, and isobutanol; Optionally, the temperature of the first heat treatment is 500-600°C, the heating rate is 1-5°C / min, and the holding time is 2-6h; Optionally, the temperature of the second heat treatment is 700-800° C., the heating rate is 1-5° C. / min, and the holding time is 1-3 hours.
14. A negative electrode plate, characterized in that: It comprises: the negative electrode material according to claim 11, or the silicon-carbon negative electrode material according to claim 12, or the silicon-carbon negative electrode material prepared by the preparation method according to claim 13.
15. A secondary battery, characterized in that: Contains the negative electrode sheet as claimed in claim 14.